A Study on the Optimum Size of Sample Plot for Forest Inventory - Ray, P. N. (Indian Forester, 1993)
Determination of optimum plot size is crucial in forest inventory design employing fixed area sampling units. The optimum plot is that which provides the greatest precision per unit cost or alternatively the least cost per unit precision. The study provides guidelines about suitability of specific plot sizes in three major forest types of Meghalaya Mate namely, Pine, Sal and Miscellaneous forests. Sample plots of increasing plot sizes were laid out in forest areas of the State and inventory was carrid out. It was found tbat variability and standard error per cent in all the three forest types diminished with increase in plot size. Due to a lesser degree of heterogeneity in Pine and Sal forests, plot size of 0.2 ha is optimum. In miscellaneous forest variability being larger, 0.3 ha stood out as the optimum plot size.